Acute Tubular Injury from Oleander (Nerium oleander) Toxicosis in an Alpaca - Behlen, Jonathan C; Lui, Clinson C; White, Sarah; Reed, Shannon; Mays, Travis; Rech, Raquel R (Brazilian Journal of Veterinary Pathology, 2024)
A 2-year-old, male alpaca was presented to the Texas A&M Large Animal Teaching Hospital with bradycardia, arrhythmia, dehydration, severe azotemia (BUN 260 mg/dl, creatinine 14.93 mg/dl), hyperphosphatemia (13.4 mg/dl), hypermagnesemia (3.4 mg/dl), mild hypokalemia (4.0 mg/dl), leukocytosis (32,500/μl) with neutrophilia (28,600/μl), acidemia, and low body condition score. The patient was placed on supportive treatment, but due to poor prognosis, the owner elected for euthanasia.